Waveband routing on logical topologies constructed over a ring network - Ganguly, S.; Varsou, A.C.; Izmailov, R. (HPSR 2004 : 2004 Workshop on High Performance Switching and Routing : Phoenix, Arizona, U.S.A., April 19-21, 2004, 2004)
Aggregation of individual wavelengths into wavebands for their subsequent switching and routing as a single group is an attractive way for scalable and cost-efficient routing in optical networks. Our objective is to minimize the switching cost by employing a waveband hierarchy subject to physical constraints. To that extent, we establish the equivalence between the waveband routing/assignment problem and the logical topology design problem. We provide a general model for logical topology design using an integer linear programming formulation. We propose a heuristic-based algorithm for the case of ring networks and use extensive simulation results to describe the performance of this algorithm towards our general goal of minimizing the switching cost.